Geography, Depreciation, and Growth - Hsiang, Solomon M.; Jina, Amir S. (American Economic Review, 2015)
It has been proposed that geography influences economic growth for many reasons. Previous analyses of comparative development seem to have sidestepped the question of location-dependent depreciation. However the construction of new measures of tropical cyclone exposure enables us to consider the potential impact of this single source of capital depreciation. Using an estimate of asset destruction due to tropical cyclones, we identify the “sandcastle depreciation” rate, and find support for location-dependent depreciation by looking at average growth rates. This leads us to propose that heterogeneous and geographically-dependent depreciation rates may play an important role in global patterns of economic development.